Ivermectin: A multilevel approach to evaluate effects in Prochilodus lineatus (Valenciennes, 1836) (Characiformes, Prochilodontidae), an inland fishery species - Lozano, Ismael Esteban (2021)
Ivermectin (IVM) is one of the most widely used antiparasitics worldwide. It is a potent and effective drug for treatment and prevention of internal and external parasitic infections of livestock and humans. IVM is excreted unchanged in manure of treated animals. Thus, residues of IVM may reach aquatic systems, affecting non-target organisms such as fish. Although the presence of IVM in aquatic environments has been reported, a multilevel approach (from cellular to behavioral responses) is necessary to determine the health of exposed organisms and the environmental risks associated. The aim of the present study was to investigate the response of the Neotropical fish Prochilodus lineatus, one of the main target species of South American freshwater fisheries, exposed to environmental concentrations of IVM: low (0.5 μg L−1) and high (1.5 μg L−1). Behavioral responses were assessed in juvenile fish and included water column use, routine swimming, total distance travelled, total activity time and Maximum swimming speed achieved during the escape response. Biochemical/oxidative stress responses assessed included brain acetylcholinesterase (AChE), catalase (CAT) and glutathione S-transferase (GST) activities; total antioxidant competence against peroxyl radicals (ACAP) and lipid oxidative damage (TBARs). Hematological biomarker responses included blood glucose levels, hematocrit, hemoglobin concentration, mean corpuscular hemoglobin, mean corpuscular hemoglobin concentration, and mean corpuscular volume. Condition factor and hepatosomatic index were also calculated. The lowest IVM concentration caused a significant decrease in GST activity and maximum swimming speed during the escape response. Multivariate analysis with biochemical/stress and behavioral data revealed overall effects of IVM treatments. This multilevel analysis shows detrimental effects related to swimming behavior and predator avoidance which could affect population size and size-structure of P. lineatus. To our knowledge this is the first attempt to assess the effects of IVM on Neotropical fishes using an integrative approach based on biomarkers from different levels of biological organization.